Makna Komunikasi Keluarga Bagi Wanita Karier: Studi Fenomenologi Mengenai Makna Komunikasi Keluarga Bagi Wanita Karier di Kota Bandung - Sofian, Ferane Aristrivani (Humaniora, 2014)
Currently, the role of women has shifted from traditional to modern roles. From just having a traditional role to bear children and take care of the household, women now have a social role which can be a career in various areas of life with higher education are supported. The role of a woman when they entered the stage of marriage seems to be so complex, when different interests collide. The method used in this study is qualitative, while the approach is phenomenology. In general, qualitative research is the process of research to understand the phenomenon, based on a tradition of research with the typical method, with the object of society's problems. There are five motives that make a career woman pursue her careeer, those are helping their husband to fulfill household living cost, apply knowledge, socialization, have their own income, and self-actualization. Having a career for career women is a gift from God and the struggle and sacrifice to support life in the form of work and creativity that benefit others. Having family for career women is a priceless gift from God in a river of happiness therefore becoming part of a family must be maintained carefully. Communicating for career women, is a real form of compassion, caring, and love to keep the marriage intact. Communicating between mother and child for career women is a real form of love and care in teaching and educating children to maintain familiarity with the child.